E-Government Transformation in Central Lombok Regency: Evaluation Based on the CIPP Model - Nugroho, Alih Aji; Sudrajat, Agus; Solihati, Keisha; Kwon, Chang Ahn (Sekolah Tinggi Ilmu Administrasi Lembaga Administrasi Negara, 2025)
This study evaluates the implementation of e-government in Central Lombok Regency by examining the gap between planned objectives and actual outcomes, using the Context, Input, Process, and Product (CIPP) evaluation model introduced by Stufflebeam. While e-government is often framed as a national-level policy, this study focuses on a concrete, time-bound local initiative the 2017–2022 E-Government Development Master Plan of Central Lombok which functions as a structured implementation program suitable for programmatic evaluation. Using a qualitative case study approach, data were collected through interviews, observations, and document analysis involving key stakeholders, particularly the Central Lombok Communication and Information Office (Diskominfo). The context evaluation revealed a mismatch between the region digital goals and its limited institutional readiness, particularly in terms of infrastructure and public digital literacy. The input evaluation showed that while planning documents and budgets were prepared, gaps remained in human resources and training capacity, with only 18.75% of officials and 30.75% of staff familiar with basic ICT. The process evaluation highlighted inconsistencies between planned targets and implementation outcomes such as the low number of agencies connected to central servers and minimal public interaction with e-government platforms. Finally, the product evaluation indicated that the program’s objectives were only partially met, with persistent challenges in system integration, inter-agency coordination, and citizen uptake of services. The study concludes that improving cross-agency collaboration, enhancing digital capacity through training and education, and promoting public awareness are essential for advancing e-government outcomes in the region. The use of the CIPP model in this context offers a systematic lens to diagnose programmatic shortcomings and generate actionable recommendations for future policy implementation.